Apám nehéz álmot ígér? A társas-érzelmi vagyon prioritásainak változása a generációváltó családi vállalkozásokban - Mosolygó-Kiss, Ágnes; Heidrich, Balázs; Chandler, Nicholas (Vezetéstudomány / Budapest Management Review, 2022)
Socioemotional wealth (SEW) theory has a dominant role among family business theories due to its distinctive characteristics compared to non-family firms. Since 2007, the SEW concept has been widely used, and has examined the uniqueness of family firms. Meanwhile, critical voices have also emerged in the international academic discourse. The goal of this study is to offer a fresh literature review of SEW focusing on its changing priorities in multigenerational family businesses. This is a research area that is falsely neglected, considering the hereditary aspirations of family businesses and their consequences on preserving family control. Based upon the findings, propositions and further research directions are established.